Navigating Identity: The Role of Self-Regulation and Meaning of Life in Adolescents - Khoirunnisa, Khoirunnisa; Nani Al Muin; Caroline Lisa Setia Wati; Erwinda, Lira (Asosiasi Asesmen Pendidikan (AAP), 2025)
This study examines the correlation between self-regulation and meaning of life among high school students. Adolescence is a crucial developmental phase characterized by identity exploration and emotional challenges, where self-regulation and life purpose play essential roles. Self-regulation refers to the ability to manage thoughts, emotions, and behaviors toward long-term goals. Meanwhile, meaning of life involves both the presence and search for purpose. This quantitative correlational research was conducted at SMA Trisoko Jakarta, involving 122 randomly selected students from a population of 176. Data were collected using validated instruments based on Zimmerman’s (1989) self-regulation theory and Steger’s (2006) meaning in life framework. Statistical analysis used Pearson’s product-moment correlation. Results showed a significant positive relationship between self-regulation and meaning of life (r = 0.741, p < 0.01), indicating a strong correlation. These findings suggest that students with higher self-regulation are more likely to experience a stronger sense of life meaning. The study underscores the importance of school-based counseling in enhancing students' self-regulation to support identity development and existential well-being.